Nitric oxide regulates non-classical secretion of tissue transglutaminase - Santhanam, Lakshmi (Landes Bioscience, 2011)
Nitric oxide (NO) is an endogenous second messenger which acts as a potent vasodilator, anti-inflammatory, anti-thrombotic and pro-angiogenic agent in the vasculature. Recent studies revealed that the effects of NO on blood vessels are mediated in part by its ability to regulate protein trafficking machinery and vesicle-based exocytosis in vascular cells. Specifically, NO-dependent S-nitrosylation of N-ethylmaleimide sensitive factor (NSF), an ATPase that enables membrane fusion, was shown to inhibit exocytosis of vesicular secretory compartments such as endothelial Weibel-Palade bodies, platelet alpha granules and cytolytic granules from activated lymphocytes. Tissue transglutaminase (tTG or TG2) is a multifunctional protein synthesized and secreted by various cell types in the vasculature, which is involved in multiple vascular diseases, including atherosclerosis, vascular calcification and age-dependent aortic stiffening. Our recent findings indicate that tTG is delivered to the cell surface and the extracellular matrix (ECM) via a non-classical ER/Golgi-independent secretion pathway, which depends on the recycling endosomes and the NSF function. Here we report that NO attenuates the unconventional secretion of tTG in human aortic endothelial cells. NO-dependent downregulation of extracellular tTG levels via inhibition of its secretion might be a part of general physiological mechanism which limits externalization of adhesive, pro-inflammatory and thrombogenic proteins in the vasculature.